2016
DOI: 10.1093/ejcts/ezw041
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell aortitis: clinical presentation and outcomes in 40 patients consecutively operated on

Abstract: GCA of the thoracic aorta may be suspected in less than 25% of patients preoperatively. Clinical presentation may be acute or chronic with localized or diffused aortic involvement but always involved the ascending aorta. Surgery may be performed with excellent outcomes. Follow-up imaging is mandatory to assess aortic progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…The risk of distal aortic disease was 11-fold in comparison to the control group [30]. The progressive aortic dilatation was noted in all levels from the arch to the infrarenal aorta after ascending aortic surgery [31].…”
Section: The Distal Aortamentioning
confidence: 83%
See 1 more Smart Citation
“…The risk of distal aortic disease was 11-fold in comparison to the control group [30]. The progressive aortic dilatation was noted in all levels from the arch to the infrarenal aorta after ascending aortic surgery [31].…”
Section: The Distal Aortamentioning
confidence: 83%
“…Aortic valve pathology was a positive predictor of inflammatory origin of the aneurysm in several studies [16][17][18]. Concomitant aortic valve surgery was performed in 51% and 80% of the patients [13,31] who had ascending aortic surgery for autoimmune aortitis. The aortic valve can be affected as a part of the systemic disease as in Cogan's syndrome and Behcet disease [41] while aortic valve affection in Takayasu is rare.…”
Section: The Aortic Valvementioning
confidence: 99%
“…With the normal aortic valve cusps viewed macroscopically, valve-sparing root replacement could be indicated. 1,7,8) Gagné-Loranger et al reported that valve sparing was performed in 16 patients (50% of aortic valve procedure). One patient required an aortic valve replacement redo owing to a recurrent aortic regurgitation 4 years after the valve-sparing procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Gagné-Loranger et al cautioned that patients with GCA may be at increased risk for endoleaks, especially when the landing zone is diseased. 1) Reports of the anastomotic pseudoaneurysm in patients with GCA were scarce compared with Takayasu arteritis. However, patients with aneurysms by GCA carry an incidence of aortic dissection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation